2022
DOI: 10.1158/0008-5472.can-21-2292
|View full text |Cite
|
Sign up to set email alerts
|

EBV Infection in Epithelial Malignancies Induces Resistance to Antitumor Natural Killer Cells via F3-Mediated Platelet Aggregation

Abstract: Nasopharyngeal carcinoma (NPC) and Epstein–Barr virus (EBV)–associated gastric carcinoma (EBVaGC) are two major EBV-associated epithelial malignancies, both of which are characterized by the infiltration of a large number of lymphocytes, including natural killer (NK) cells. Although NK cells can prevent the development of EBV-associated epithelial malignancies, EBV-infected tumor cells often develop resistance to surveillance by NK cells. Elucidating the interactions between NK cells and EBV-infected tumor cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Although a tendency toward decreased platelets is frequently observed in acute EBV infection ( 30 ), we noted a substantially increased level of PLT in EBVaGC. In a recent study on nasopharyngeal carcinoma and EBVaGC, EBV was reported to induce F3-mediated PLT aggregation that inhibited the antitumor function of natural killer cells ( 31 ). In the current study, we also noted a tendency for an elevation in inflammatory CRP in EBVaGC.…”
Section: Discussionmentioning
confidence: 99%
“…Although a tendency toward decreased platelets is frequently observed in acute EBV infection ( 30 ), we noted a substantially increased level of PLT in EBVaGC. In a recent study on nasopharyngeal carcinoma and EBVaGC, EBV was reported to induce F3-mediated PLT aggregation that inhibited the antitumor function of natural killer cells ( 31 ). In the current study, we also noted a tendency for an elevation in inflammatory CRP in EBVaGC.…”
Section: Discussionmentioning
confidence: 99%
“…Our team has been actively developing new approaches and targets for the treatment of EBV-NPC. We found that after EBV infection, LMP2A induced the upregulation of F3 expression and was associated with the dysfunction of NK cells in NPC (2). We used a combination of F3 inhibitor and NK cell adoptive therapy and achieved a considerable therapeutic effect in a mouse model of NPC.…”
Section: Nk Cell Therapymentioning
confidence: 99%
“…Approximately 95% of the global population are EBV asymptomatic carriers ( 1 , 2 ). EBV primarily infects epithelial and B cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NKs can target EBV-infected cells that are in the lytic replication phase and maintain the homeostasis of the host immune system [43,44]. A recent study found that LMP2A inhibited NK cell function through platelet aggregation by platelet factor 3, which offers a novel candidate for the development of NK cell immunotherapy [45]. EBV miRNAs have been confirmed to mediate the escape of NK cell killing by down-regulating NKG2D ligand and target pro-apoptotic proteins such as PUMA to resist NK cell cytotoxity [46][47][48][49].…”
Section: Npc Crosstalk Leading To Immune Escape Direct Cell-cell Cont...mentioning
confidence: 99%